Visual teams : graphic tools for commitment, innovation, & high performance - Sibbet David (Hoboken, NJ: John Wiley & Sons, 2011)
Graphic tools and strategies for creating teams and sustaining results, whether you are co-located or spread around the world. A design approach is used for building and leading a team.
Includes bibliographical references (p. 265-272) and index.
Keywords: Visual communication; Teams in the workplace; Decision making